Formal solutions of completely integrable Pfaffian systems with normal crossings. (July 2017) - Barkatou, Moulay A.; Jaroschek, Maximilian; Maddah, Suzy S.
Abstract: In this paper, we present an algorithm for computing a fundamental matrix of formal solutions of completely integrable Pfaffian systems with normal crossings in several variables. This algorithm is a generalization of a method developed for the bivariate case based on a combination of several reduction techniques and is partially 2 implemented in the computer algebra systemMaple .